Misconceptions, Diagnostic Instruments Used and Their Causes in Chemistry Learning: Literature Review - Himatul Aliyah; Akhmad Fauzi; Madina Alfi Manaroh (Postgraduate, University of Mataram, 2025)
This study aims to analyze and provide an overview of the micsconceptions experienced by students, the diagnostic instruments used and their causes in chemistry learning. The research method used was literature review. The research data consisted of 20 relevant national and international articles in the range of 2019-2025. The articles selected have similar topics of discussion regarding misconception analysis in chemistry learning. The results showed that the research on misconceptions in chemistry learning mostly frequently found in the concept of acid-base and salt hydrolysis, reaction rates and chemical equilibrium, thermochemistry, and chemical bonding. The diagnostic instruments used include two-tier tests, three-tier tests, four-tier tests, five-tier tests, questionnaires, multiple-choice questions and interviews. Factors causing misconceptions are due to internal and external factors. Internal factors include the discrepancy between students' preconceptions and experts' knowledge concepts, while external factors include learning methods and teaching materials used by teachers. In addition, there is no significant difference between the instrument used and the misconceptions found across countries. So that the trend of misconception research is a study that deserves to continue to be developed and researched